Sepsis-induced changes in differentiation, maintenance, and function of memory CD8 T cell subsets - Heidarian, Mohammad; Griffith, Thomas S.; Badovinac, Vladimir P. (Frontiers in Immunology, 2023)
Formation of long-lasting memory lymphocytes is one of the foundational characteristics of adaptive immunity and the basis of many vaccination strategies. Following the rapid expansion and contraction of effector CD8 T cells, the surviving antigen (Ag)-specific cells give rise to the memory CD8 T cells that persist for a long time and are phenotypically and functionally distinct from their naïve counterparts. Significant heterogeneity exists within the memory CD8 T cell pool, as different subsets display distinct tissue localization preferences, cytotoxic ability, and proliferative capacity, but all memory CD8 T cells are equipped to mount an enhanced immune response upon Ag re-encounter. Memory CD8 T cells demonstrate numerical stability under homeostatic conditions, but sepsis causes a significant decline in the number of memory CD8 T cells and diminishes their Ag-dependent and -independent functions. Sepsis also rewires the transcriptional profile of memory CD8 T cells, which profoundly impacts memory CD8 T cell differentiation and, ultimately, the protective capacity of memory CD8 T cells upon subsequent stimulation. This review delves into different aspects of memory CD8 T cell subsets as well as the immediate and long-term impact of sepsis on memory CD8 T cell biology